Social Security of Population as a Basis for Stable Growth of Border Regions - Bilczak, Wasyl; Bilczak, Michał (Olsztyn Economic Journal, 2016)
This article presents the issues of social development and social protection in border regions. An extensive analytical study shows that taking effective actions on social protection and social development is the basis of stable development of border regions. Theoretical foundations of social protection of the population were also presented. Using the example of national programs of social protection of the population in developed countries, the main directions of social protection of the population were examined. This paper also includes an assessment of capabilities and resource bases and their impact on the social protection of the population, a combination of cash and in-kind funds required to meet human needs and the functioning of the entire system of social protection of the population in border regions.